Microsatellite typing of Aedes albopictus (Diptera Culicidae) populations from Germany suggests regular introductions - Lühken, Renke; Heitmann, Anna; Jansen, Stephanie; Schmidt-Chanasit, Jonas; Börstler, Jessica; Werner, Doreen; Kampen, Helge; Kuhn, Carola; Pluskota, Björn; Ferstl, Ina; Jöst, Artur; Becker, Norbert; et al. (Infection, genetics and evolution, 2020)
The global spread of the Asian tiger mosquito Aedes albopictus is of concern, as this mosquito species constitutes an important vector of a number of emerging pathogens including dengue virus, chikungunya virus and Zika virus. Since its first appearance in Albania (1979) and Italy (1990), the species has been reported from more than twenty-five European countries. However, the dispersion process in Europe is largely unknown, as information on population genetic structure is lacking, which is relevant to understand the observed spread. In order to determine whether the ten Ae. albopictus populations detected in Germany until 2017 originate from a single introduction event or from independent importations, genetic analyses with a set of sixteen microsatellite markers were performed. The samples included specimens from three locations with potentially overwintering populations, collected in three consecutive years. The results indicate a heterogeneous population structure consisting of two clusters with significant substructuring, suggesting regular, independent introductions instead of a continuous spread across Germany originating from one or few sites. Moreover, the analyses provide further evidence for Ae. albopictus overwintering in Germany as samples from identical locations collected in three consecutive years had a relatively high genetic similarity. However, the population structure is probably influenced by local mosquito control activities. The results presented provide further evidence for regular introductions of Ae. albopictus specimens into Germany, probably leading to local establishment north of the Alps. This highlights the need for constant surveillance and control of Ae. albopictus not only in southern, but also in Central Europe.
Gesehen am 02.07.2020